The Influence of Brand Image on Purchasing Decisions at Lazada Among Management Students at Universitas Insan Pembangunan Indonesia - FITRIDIANI, Mutiara; SIHOMBING, Yusniati; DAMAYANTI, Monica; HADDY, Muhammad Saeful; KUSNIYANTO, Royan (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to determine the effect of brand image on purchasing decisions on the Lazada e-commerce platform. The study was conducted on 8th semester Management students at Universitas Insan Pembangunan Indonesia who actively use the Lazada application. The research method used was quantitative with purposive sampling, involving 100 respondents. Data was collected through a closed questionnaire and analyzed using SPSS 26. The results of the study indicate that brand image significantly influences purchasing decisions, with a t-value of 4.273 > t-table 1.984 and significance of 0.000 < 0.05. The coefficient of determination (R²) is 0.203, meaning that brand image contributes 20.3% to purchasing decisions.